2017
DOI: 10.1158/0008-5472.can-17-0569
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-Signal Transduction in Mesenchymal Stem Cells Induces Prosaposin Secretion to Drive the Proliferation of Breast Cancer Cells

Abstract: In response to chemical stimuli from cancer cells, mesenchymal stem cells (MSC) can differentiate into cancer-associated fibroblasts (CAF) and promote tumor progression. How mechanical stimuli such as stiffness of the extracellular matrix (ECM) contribute to MSC phenotype in cancer remains poorly understood. Here we show that ECM stiffness leads to mechano-signal transduction in MSC which promotes mammary tumor growth in part through secretion of the signaling protein prosaposin. On a stiff matrix, MSC culture… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 42 publications
0
70
0
Order By: Relevance
“…We successfully propagated eight human GSC lines with four different molecular subtypes and found the highest PSAP expression and secretion in mesenchymal GSCs, as determined by western blotting and ELISA. It has previously been shown that chemical or mechanical stimulation of breast cancer can promote the mesenchymal stem cells in the tumor microenvironment to produce a large amount of PSAP, which can induce the proliferation and invasion of breast cancer cells [16,41]. Combined with the results of this study, we speculated that the abnormally elevated levels of PSAP in mesenchymal GBM may be expressed and secreted from GSCs and may promote the growth or invasion of GSCs or glioma cells through a paracrine or autocrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We successfully propagated eight human GSC lines with four different molecular subtypes and found the highest PSAP expression and secretion in mesenchymal GSCs, as determined by western blotting and ELISA. It has previously been shown that chemical or mechanical stimulation of breast cancer can promote the mesenchymal stem cells in the tumor microenvironment to produce a large amount of PSAP, which can induce the proliferation and invasion of breast cancer cells [16,41]. Combined with the results of this study, we speculated that the abnormally elevated levels of PSAP in mesenchymal GBM may be expressed and secreted from GSCs and may promote the growth or invasion of GSCs or glioma cells through a paracrine or autocrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating the expression of PSAP in GSCs and glioma cell lines, we found that the invasiveness of mesenchymal M177 GSCs and U87 glioma cells were greatly weakened after PSAP knockdown; the opposite results were observed after PSAP overexpression. Although several studies have reported that PSAP promotes the invasion and metastasis of prostate and breast cancer [13][14][15][16], the opposite conclusions have also been reported that PSAP can stimulate the production of TSP-1 (encoded by THBS1) in the tumor microenvironment of breast, prostate, lung and ovarian cancer [42,43]. TSP-1 can inhibit angiogenesis and induce tumor cell apoptosis via the cell surface receptor CD36 [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the remodeling that induces these changes can occur for a number of reasons: For mammary cancers, tumors "feel" stiffer during manual palpation (8) in part from increased ECM expression and cross-linking (9, 10) as well as changes in protein composition (11,12). This dynamic tumor microenvironment is established by tumor and stromal cells and their soluble factors (13)(14)(15), which evolve as the tumor progresses over months to years (8). Animal models largely recapitulate the dynamics of human tumors, e.g., stiffening by lysyl oxidase-mediated cross-linking (9), but they remain exceedingly complex.…”
mentioning
confidence: 99%
“…3 Parameters that affect stromal micromechanical properties, such as collagen content, organization, and cross-links, are of particular interest since important mechanosignaling pathways have already been identified that affect disease development and metastasis. [4][5][6][7][8] Further, tissue stiffening and increases in mammographic tissue density are established breast cancer diagnostic markers. The content and organization of collagen fibers are key contributors to tissue stiffness and density and distinct tumor-associated collagen organization features have been identified at various stages of breast cancer development.…”
Section: Introductionmentioning
confidence: 99%